Nanoscaled porphyrinic metal–organic frameworks: photosensitizer delivery systems for photodynamic therapy. Issue 9 (16th February 2017) - Bůžek, Daniel; Zelenka, Jaroslav; Ulbrich, Pavel; Ruml, Tomáš; Křížová, Ivana; Lang, Jan; Kubát, Pavel; Demel, Jan; Kirakci, Kaplan; Lang, Kamil
Abstract : PCN-222/MOF-545 nanoparticles cause apoptosis of cancer cells upon visible light irradiation. The phototoxicity of the nanoparticles is deactivated after several hours, which is an attractive feature to avoid post-treatment photosensitization issues. Abstract : The photocytotoxic activity of porphyrin-containing materials including metal–organic frameworks (MOFs) has attracted ever increasing interest. We have developed a simple synthesis of hexagonal PCN-222/MOF-545 nanoparticles, which are powerful in inducing reactive oxygen species-mediated apoptosis of cancer cells upon visible light irradiation. The extent of the cytotoxic effect well correlates with the nanoparticle size and structural instability. High phototoxicity of the presented nanoparticles and their deactivation within several hours open up the door to possible applications in cancer therapy.